O falso documentário - Emérito, Matheus Barbosa (2008)
This study has as its purpose the examination of a specific mode of representation: the fake documentary at its supports - television and cinema. Among hypothesis adopted, fake documentary has been analyzed as convention anti-normative in the face of its fiction predominance in a non-fiction body (discursive code) and its capacity to incorporate the documentary aspect of faith. Its creation agenda tends to deconstruct its significant, but in the other hand, can celebrate it by making parody. For all that matter, we pretend to assess and conceptualize documentary as a cinema genre to support the fake documentary definitions. Works of theorists as Bill Nichols were analyzed. Nichols made serious contributions to institute documentary as genre by texts which discuss since the cinema beginning to the emergence of documentary peculiar format structures. Fake documentary definitions were assessed having in its bases the study of Jane Roscoe and Craig Hight, who considered fake documentary as a fiction which works as non-fiction. However, it is necessary to inspect the documentary practices at television in order to adapt it into the concept. In this way, a disposition based on Arlindo Machado suggestion of television genre categories was organized: forms based on dialog; narrative in series; television news; live transmission. As for purpose to classify fake documentary, we discussed the possibility to divide it into two categories: parody and hoax. Studies of Linda Hutcheon defend that parody can only perform its function when recognized as something distinct from original. In opposite, hoax takes place as a parody not interpreted. This research had as its corpus: cinema movies which attend as fake documentaries. Specifically, the british movie called The War Game (Peter Watkins, 1965) was analyzed with more profundity aiming to verify the hypothesis adopted